Distribution of green spaces across socio-economic groups: a study of Bhubaneswar, India - Dash, Monalipa; Chakraborty, Manjari (Journal of Architecture and Urbanism, 2023)
Urban green spaces (UGS) are linked with numerous health benefits. However, recent studies have highlighted an increased level of disparity in their distribution across different socio-economic groups. Adequate number of UGS and their size play an important role to achieve spatial equity. The purpose of this study is to analyze the availability of UGS across all socio-economic groups of Bhubaneswar, Orissa, India. Methods: The socio-economic groups are created by using the ward level socio-economic census data of Bhubaneswar and and PCA method of analysis. The UGS are identified using satellite images if they fulfil the criteria such as: named as a park or garden and has a definitive boundary in the year 2021. A one-way ANOVA is used for the analysis. Result: The study revealed a non-uniform distribution; 27 out of 67 wards do not have any form of parks in their vicinity. From the equity point of view, the UGS distribution is examined for parks and overall UGS. There is no major difference found in terms of availability of parks in different SES statistically. However, park area average is observed to be the higher in middle deprived communities (26738.32 m2/neighborhood) followed by least deprived communities (22386.7378 m2/neighborhood) but the average number of parks seem to be the lowest in the least deprived communities (1 park/neighborhood). The land allocation per capita for overall UGS came to be the highest for the most deprived neighborhoods (0.0146 km2/1000 population). The bigger UGS are in the most deprived wards probably because there is availability of land and low population density.